The manifestation of the green agenda: a comparative analysis of parliamentary debates. Issue 6 (19th September 2021) - Debus, Marc; Tosun, Jale
ABSTRACT: Parliamentary debates are an important instrument for setting the political agenda. We hypothesize that parliamentarians belonging to a Green party deliver more speeches on issues related not only to the environment, but also to agriculture, energy and transport as well as to citizen and minority rights. We conceptualize this mix of policy issues as the green agenda. Research on the programmatic-ideological position of political parties has shown that such a broader green agenda exists. Can we also observe this green agenda in parliamentary debates? Does the manifestation of the green agenda depend on the representation of political groups in parliament? By drawing on original data for parliamentary debates in the Czech Republic, Finland, Germany, Ireland, and Sweden, we show that Green parties in parliament push forward issues related to the broader green agenda, though it is also affected by the representation of Agrarian parties.